Waves that carry national language. The Lecciones of Florencio Garrigós at the Escuela del Aire (Anclajes, 2021)
In 1940, the Argentine journalist, grammarian and teacher Florencio Garrigós published his Lecciones de idioma nacional. Within the framework of linguistic historiography, we aim to analyze the specific features that this work presents in the history of Argentine school grammar. To do this, we first reconstruct the professional career of its author; then, we present the Escuela del Aire, the first distance education experience that used the radio in Argentina. Finally, we analyze the text of the Lecciones, and argue that it is an innovative work in at least two senses: because of the didactic innovation that it proposes and because of the defined perspective it adopts regarding the Argentinian linguistic variation phenomena, which it values ​​positively.
Keywords: Florencio Garrigós; Escuela del Aire; Argentinian school grammar; twentieth century; linguistic historiography